Jazz and audiovisual narrative. The soundtrack of Los inocentes (1963) by Isidro Maiztegui (Revista Argentina de Musicología, 2019)
Isidro Maiztegui was one of the most outstanding composers of film music of Argentina and Spain between the thirties and the sixties. The arrival of Maiztegui to Spain in the 1950s coincides with the impetuous emergence of Juan Antonio Bardem’s cinema, and the Argentine composer became the main musician of the Spanish director. Los inocentes (1963), a Spanish-Argentine co-production filmed in Mar del Plata with an argument and an aesthetic close to film noir, is the last collaboration between the artists and is part of the new cinema that was appearing in both countries at that time.For this film Maiztegui composes a soundtrack in a language between cool jazz and modal jazz. The music of this film shows the consolidation in the use of the expressive resources from previous stages and, at the same time, the evolution of his compositive style. From this contextualization we are going to analyze the presence of urban popular music in the audiovisual narrative of the film and the relation established between music, image and its internal narrative structure.
Keywords: Isidro Maiztegui; Juan Antonio Bardem; Los inocentes; film music; Spanish-Argentine cinema